2019
DOI: 10.1186/s12864-019-5547-y
|View full text |Cite
|
Sign up to set email alerts
|

De novo comparative transcriptome analysis of a rare cicada, with identification of candidate genes related to adaptation to a novel host plant and drier habitats

Abstract: Background: Although the importance of host plant chemistry in plant-insect interactions is widely recognized, our understanding about the genetic basis underlying the relationship between changes in midgut proteins and adaptation of plant-feeding insects to novel host plants and habitats is very limited. To address this knowledge gap, the transcriptional profiles of midguts among three populations of the cicada Subpsaltria yangi Chen were compared. Among which, the Hancheng (HC) and Fengxiang (FX) populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 92 publications
(111 reference statements)
1
11
0
Order By: Relevance
“…Molecular identification of cytochrome c oxidase subunit I ( COI ) sequence distances of sampled individuals from the two sites were between 0.0 and 0.00897, indicating little genetic divergence between M. saltuarius populations. Previously, similar results have been reported from comparable sampling strategies [ 26 , 30 , 80 ]. Therefore, the different gene expression patterns detected in the present study may be mainly caused by host plant diet.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Molecular identification of cytochrome c oxidase subunit I ( COI ) sequence distances of sampled individuals from the two sites were between 0.0 and 0.00897, indicating little genetic divergence between M. saltuarius populations. Previously, similar results have been reported from comparable sampling strategies [ 26 , 30 , 80 ]. Therefore, the different gene expression patterns detected in the present study may be mainly caused by host plant diet.…”
Section: Discussionsupporting
confidence: 87%
“…Xu et al [ 62 ] found that the VOCs from P. koraiensis included α-pinene, β-pinene, and sabinene. Insects can successfully survive on their host plants by producing detoxifying enzymes, e.g., P450s, UGTs, and CEs [ 25 , 30 , 41 ]. In the present study, we found that 11 P450, seven CE, and three UGT, and most of them were upregulated in the larvae feeding on P. tabuliformis compared with P. koraiensis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that defensive enzymes can be involved in the differentiation of pea aphid biotypes [13,55]. In addition, differences in the expression of genes related to detoxification were also detected between Subpsaltria yangi populations specialized on different host plants with variable compositions and concentrations of secondary plant compounds [59,60]. Therefore, all the above-mentioned defense-related common DEGs may play important roles in the divergence of S. avenae biotypes.…”
Section: Divergence Of Aphid Biotypesmentioning
confidence: 94%
“…Although digestion- and detoxification-related genes (such as genes of ‘lysosome’, ‘drug metabolism cytochrome P450 ’, and ‘metabolism of xenobiotics by cytochrome P450 ’) were also enriched in the sample comparisons for those feeding on banana in this study ( Table 4 ), these genes did not show the largest effects associated with banana use by B. tau . In addition, results of studies related novel host use in a cicada revealed that digestion-, detoxification-, oxidation-reduction-, water-deprivation-related genes regulated host adaptation ( Hou and Wei 2019 ). Here, we show that B. tau feeding on different hosts will face various nutrients and chemical constituents produced by different host plants ( Vogel et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%